Development of a Passive Check Valve for Cryogenic Applications - Moore, Bradley (Proceedings of the Wisconsin Space Conference, 2012)
Future astrophysics missions will rely on a new generation of cooling technologies to improve the resolution of infrared and x-ray sensors. A novel continuous cold cycle dilution refrigerator (CCDR) has been proposed by Prof. F.K. Miller to provide cooling for these sensors at temperatures below 100mK. A passive check valve for liquid 4He-3He mixtures is a key technological innovation required to implement the CCDR, as will be further explained in the paper. The design of a reed style passive check valve and initial results from tests with helium gas at room temperature and 80K will be detailed.Â